The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4049/jimmunol.0902942
|View full text |Cite
|
Sign up to set email alerts
|

IgE Transcripts in the Circulation of Allergic Children Reflect a Classical Antigen-Driven B Cell Response and Not a Superantigen-Like Activation

Abstract: Allergic asthma is the most frequent chronic disorder in childhood. Although IgE is a central effector molecule in allergic diseases, the nature of the IgE response is still under debate. The objective of our study was to clarify whether the IgE repertoire in the circulation of allergic children represents a classical Ag-driven and oligoclonal B cell response, a superantigen-like activation of a subset of B cells, or a polyclonal B-1 cell expansion. Using a highly sensitive RT-PCR method, we amplified, cloned,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 36 publications
6
64
2
Order By: Relevance
“…Moreover, IgG4 can also mediate autoimmunity (e.g., pemphigus vulgaris) and might play a pathogenic role in newly identified "IgG4-related disease" (34). We have shown that, in contrast to earlier assumptions, the IgE transcripts in PBMCs of allergic children reflect a classical Ag-driven B2 cell response and not a B1 cell response or a superantigen-like activation (35). Even in the absence of Ag, B1 cells spontaneously secrete "natural" Abs that are more "germline-like" because of minimal N-region addition and low somatic mutation frequency compared with B2 cell-derived Igs (36).…”
contrasting
confidence: 47%
See 4 more Smart Citations
“…Moreover, IgG4 can also mediate autoimmunity (e.g., pemphigus vulgaris) and might play a pathogenic role in newly identified "IgG4-related disease" (34). We have shown that, in contrast to earlier assumptions, the IgE transcripts in PBMCs of allergic children reflect a classical Ag-driven B2 cell response and not a B1 cell response or a superantigen-like activation (35). Even in the absence of Ag, B1 cells spontaneously secrete "natural" Abs that are more "germline-like" because of minimal N-region addition and low somatic mutation frequency compared with B2 cell-derived Igs (36).…”
contrasting
confidence: 47%
“…As a reference, we used 341 previously published unique V H DJ H C ε sequences (IgE transcripts) from the same blood samples (GenBank accession nos. FJ840062-FJ840439) (35).…”
Section: Characterization Of Igg4 Transcriptsmentioning
confidence: 99%
See 3 more Smart Citations